"Came for the horses, stayed for the men": A mixed methods analysis of staff, community, and reentrant perceptions of a prison-equine program (PEP). Issue 3 (2nd April 2020) - Morgan, Amy A.; Arditti, Joyce A.; Spiers, Sara; Buechner-Maxwell, Virginia; Shivey, Victoria
Abstract: Prison-equine programs (PEPs) appear to play a role in rehabilitating incarcerated persons (IPs) by teaching equine and farrier skills, as well as promoting therapeutic effects through the human-animal bond. Using a mixed-methods approach guided by ecological theory, the present study explored the perceptions of PEP staff, graduates, and community members attending a public PEP event. Findings from both thematic qualitative analysis and descriptive quantitative results indicated that community members reported significantly less stigma toward PEP participants than general IPs. Focus group results with PEP staff indicated personal transformation through witnessing PEP participant rehabilitation. Interviews with PEP graduates (i.e., reentrants) identified relationships with staff and peers, as well as the barn environment, in maintaining positive change during reentry. Findings are represented by four themes: Experiencing change, Witnessing change, Mechanisms of change, and Future of the program. These findings are the first to highlight how person-environment interactions create important mesosystem links that may promote development, prime positive reentry scenarios, and enable stakeholder support of PEPs across ecological levels.